Will womankind now go hunting? Constructions of gender in the Aqhat Epic - McDonnell Jr, Eric D. (Antiguo Oriente, 2021)
Though the study of gender in ancient texts is fraught with difficulty, the Ugaritic Aqhat Epic lends itself to a literary analysis through the constructions of gender explicitly operative in the text. This article analyzes the four repetitions of the list of familial duties prescribed for the ideal son (Aqhat) and traces the ways these explicitly gendered duties are performed by two prominent female characters (Pughat and Anat). In light of the narrative’s subversion of the gendered expectations set up in the beginning of the narrative, the article concludes with a brief reflection on the role of the epic-verse tradition in Ugaritic society.